2021
DOI: 10.1108/ijqss-02-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Patient hospital experience and satisfaction on social media

Abstract: Purpose The purpose of this paper is to show the value of open-ended narrative patient reviews on social media for elucidating aspects of hospital patient satisfaction. Design/methodology/approach Mixed methods analyses using qualitative (manual content analyses using grounded theory and algorithmic analyses using the Natural Language Toolkit) followed by quantitative analyses (negative binomial regression). Findings Health-care team communication, health-care team action orientation and patient hospital r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
2
1
Order By: Relevance
“…The results of the SEM analysis demonstrated that satisfaction with the quality of treatment provided (β = 0.538) and satisfaction with leaving the hospital (β = 0.547) were the factors that have a lower direct impact on the patient’s overall satisfaction with the healthcare provided. This is slightly contrary to many studies suggesting that the satisfaction of hospitalised patients is related to the quality of healthcare, diagnosis and treatment processes ([ 21 , 23 , 24 , 30 , 56 ]). This fact can also be explained by the results of the study by Farzianpour et al [ 16 ], who considered patient satisfaction as a cognitive response influenced by various factors.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The results of the SEM analysis demonstrated that satisfaction with the quality of treatment provided (β = 0.538) and satisfaction with leaving the hospital (β = 0.547) were the factors that have a lower direct impact on the patient’s overall satisfaction with the healthcare provided. This is slightly contrary to many studies suggesting that the satisfaction of hospitalised patients is related to the quality of healthcare, diagnosis and treatment processes ([ 21 , 23 , 24 , 30 , 56 ]). This fact can also be explained by the results of the study by Farzianpour et al [ 16 ], who considered patient satisfaction as a cognitive response influenced by various factors.…”
Section: Discussioncontrasting
confidence: 94%
“…Open narrative reviews of the patients in social media can also be an important source of information to shed light on the important aspects of patient satisfaction in hospitals. This aspect was verified in the research study by Chakraborty and Church [ 29 , 30 , 31 ]. This is a unique study, where the authors used the qualitative and quantitative methods to evaluate the comments on the reviews of hospitalisations of the respondents that were freely made public on the social networks.…”
Section: Background Of the Studysupporting
confidence: 61%
See 1 more Smart Citation
“…In marketing, experience has been considered a key concept that has relationships with other concepts such as brand loyalty, 22 , 23 satisfaction, 24 , 25 and brand equity. 26 , 27 Customer experience is a customer’s cognitive, emotional, behavioral, sensorial, and social responses to a firm’s offerings during the customer’s entire purchase journey.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%